b - Forum on Women in Security and International Affairs (Bangladesh); Bangladesh Freedom Foundation (Dhaka : Forum on Women in Security and International Affairs, 2006)
Contributed articles on businesswomen and provisions for their advancement and social security in Bangladesh.
"Sponsored by Bangladesh Freedom Foundation."
General
Bengali and English.
Keywords: Businesswomen -- Bangladesh; Social security -- Law and legislation -- Bangladesh; Businesswomen -- Legal status, laws, etc -- Bangladesh